THE EFFECT OF AUDIO LIGUAL METHOD (ALM) IN MANDALORIAN MOVIES ON LISTENING ABILITY IN 11TH STUDENT OF SMA 12 BENGKULU UTARA - aji sawitriyansyah; Waslurachim Safitri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Nowadays, teaching media is developed well in many kinds especially for English listening skill. Listening is the first communication skill human acquired. It is an important process which has vital role in the daily activity. The example of teaching media to be used in listening class is English Movie. The researcher conducted watching English movie activity in the class and he realize that the teaching media is interesting to be used because students are easy to get bored when they have listening activity without visual media. Then, he wants to know the students’ perception about the use of this method, The objective of the research was to find out the Effect of Audio Lingual Method (ALM) In Mandalorian Movies On Listening Ability and it was using quantitative experimental research. The population of this research was the students in SMA 12 Bengkulu Utara. It takes 60 students consisted of 30 as experimental and 30 as a control class. The result of t-test value of the post test was greater than t-table value (116,0>2.042). The hypothesis testing above showed that the listening comprehension scores of the students in experimental group had a significant difference after the use ALM (Audio Lingual Method) in Mandalorian movies, strategy was done in compared to the control’s group achievement who did not receive the ALM (Audio Lingual Method) in Mandalorian movies as on the experimental group, it showed Audio Lingual Method (ALM) In Mandalorian Movies On Listening Ability was effective to be used to improved students’ ability in listening. By using this strategy, it maybe improves students to learn proper English by using a movie as a learning method so the student can enjoy studying a English by watching a movie. Keywords: Listening Ability, Audio Lingual Method (ALM), Mandalorian Movie